2013
DOI: 10.5194/angeo-31-1681-2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced EISCAT UHF backscatter during high-energy auroral electron precipitation

Abstract: Abstract. Natural enhancements in the backscattered power of incoherent scatter radars up to 5 orders of magnitudes above the thermal backscatter are sometimes observed at high latitudes. Recently observations of enhancements in the backscattered power including a feature at zero Doppler shift have been reported. These enhancements are limited in altitude to tens of kilometers. The zero Doppler shift feature has been interpreted as a signature of electron density cavitation. Enhanced plasma lines during these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…Sullivan et al, 2008), the SLT-like anomalous echoes in this study were found to be closely related to energetic precipitation, characteristic of discrete aurora. This is in accordance with the event study of a similar zero Doppler shift feature seen during high-energy precipitation discussed by Schlatter et al (2013). However, modelling studies (Isham et al, 2012;Akbari et al, 2016) point to the low energy part of the electron spectrum as being efficient in exciting the Langmuir turbulence.…”
Section: Discussionsupporting
confidence: 89%
“…Sullivan et al, 2008), the SLT-like anomalous echoes in this study were found to be closely related to energetic precipitation, characteristic of discrete aurora. This is in accordance with the event study of a similar zero Doppler shift feature seen during high-energy precipitation discussed by Schlatter et al (2013). However, modelling studies (Isham et al, 2012;Akbari et al, 2016) point to the low energy part of the electron spectrum as being efficient in exciting the Langmuir turbulence.…”
Section: Discussionsupporting
confidence: 89%
“…The vertical extent of these structures has not been investigated systematically, although several examples of density enhancements associated with these structures have been presented. Thus Schlatter et al (2013) examined density enhancements due to high-energy auroral precipitation in the E and F region between ∼ 100 and ∼ 150 km; see their Fig. 1a.…”
Section: Discussionmentioning
confidence: 99%
“…Such events are referred to as naturally enhanced ion acoustic lines (NEIALs) [ Foster et al , ; Michell et al , ; Michell and Samara , ; Kontar and Pėcseli , ; Strømme et al , ]. NEIALs are captured as echoes which enhance one or both ion line shoulders in the typical power spectrum by 1–2 orders of magnitude [ Rietveld et al , ; Collis et al , ], and enhancements up to 5 orders of magnitude have been reported as well [ Schlatter et al , ]. NEIALs have been observed in field‐aligned measurements of incoherent scatter radars (ISRs).…”
Section: Introductionmentioning
confidence: 99%